Suggestions for radiation oncologists to overcome radiotherapy interruption in patients with nasopharyngeal cancer - Lee, Jung Ae; Yoon, Won Sup (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
In this issue of Radiotherapy and Oncology, Yao and colleagues report the results of intensity-modulated radiation therapy (IMRT) interruption in patients with nasopharyngeal carcinoma based on big-data intelligence platform analysis including 7,826 patients (1). They showed that increasing radiotherapy (RT) interruption to 7 or more days was significantly negative for survival.